STUDI POWER WHEELING DIKAWASAN INDUSTRI JABABEKA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Electricity Jababeka industrialarea is provided by PT Bekasi Power through 150 kV PLN's own transmission with Power Wheeling concept that is the joint utilization of transmission system which has a few definitions, for example, the utilization of transmission or distribution system to transmit electric power from existing entities and to different entities.Or sending electrical power from the seller to the buyer through a system claimed by third party. In the concept of wheeling, the fees charged for services provide and bear the lossesdue to the utilization of ipower transmission networks in this study will examine the concept of appropriate power wheeling for Applied in Jababeka industrial area